Adverse effects of the use of solid fuels on health outcomes in Chile - Gabriela Zapata-Romána; Valeria Scapini (Economics of Energy and Environmental Policy, 2026)
This study provides nationally representative evidence on the health effects of household solid fuel use in Chile, where firewood remains a common heating source despite high electrification. Using pooled CASEN microdata for 2015, 2017, and 2022, we estimate the Average Treatment Effect on the Treated (ATT) of living in a solid-fuel household on multiple morbidity indicators. To strengthen identification in repeated cross-sections and ensure comparisons are made within common support, we apply Coarsened Exact Matching (CEM) on key socioeconomic, housing, territorial, and survey-year characteristics, and estimate weighted post-matching linear probability models with household-clustered standard errors. Using self-reported morbidity and medical-treatment indicators, we find that solid-fuel use is associated with higher probabilities of recent illness (+2.14 pp) and treated morbidity, with the most consistent evidence for chronic systemic conditions (+0.49 pp) and weaker but positive evidence for cardiovascular conditions (+0.46 pp). These estimates reflect differences in health outcomes between comparable matched groups rather than cumulative long-run exposure effects. Heterogeneity analyses suggest that effects are more consistently concentrated among women and working-age adults, and that estimates vary meaningfully across macro-zones. Overall, the findings highlight household solid-fuel use as a relevant and unequal source of health risk in Chile, and point to the value of policies that facilitate cleaner residential heating and reduce exposure among vulnerable groups.